Cumulative dietary risk assessment of chronic acetylcholinesterase inhibition by residues of pesticides. (10th February 2021) - ,; Anastassiadou, Maria; Choi, Judy; Coja, Tamara; Dujardin, Bruno; Hart, Andy; Hernandez‐Jerrez, Antonio F; Jarrah, Samira; Lostia, Alfonso; Machera, Kyriaki; Mangas, Iris; Mienne, Alexandra; et al.
Abstract: A retrospective cumulative risk assessment of dietary exposure to pesticide residues was conducted for chronic inhibition of acetylcholinesterase. The pesticides considered in this assessment were identified and characterised in a previous scientific report on the establishment of cumulative assessment groups of pesticides for their effects on the nervous system. The exposure assessments used monitoring data collected by Member States under their official pesticide monitoring programmes in 2016, 2017 and 2018, and individual food consumption data from 10 populations of consumers from different countries and from different age groups. Exposure estimates were obtained by means of a two‐dimensional probabilistic model, which was implemented in SAS ® software. The characterisation of cumulative risk was supported by an uncertainty analysis based on expert knowledge elicitation. For each of the 10 populations, it is concluded with varying degrees of certainty that cumulative exposure to pesticides contributing to the chronic inhibition of acetylcholinesterase does not exceed the threshold for regulatory consideration established by risk managers.